Upaya Kemandirian Benih di Desa Sumbersalak Ledokombo Kabupaten Jember, Melalui Kegiatan Pengabdian Masyarakat - Ummi Sholikhah; Ahmad Ilham Tanzil; Wahyu Indra Duwi Fanata; Tri Ratnasari (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Implementation of community service regarding plant breeding was carried out in Sumbersalak Village, Ledokombo District with the Kenconowungu farmer group. The activities in this service program are to provide knowledge and understanding related to rice plant breeding. Breeding is carried out by crossing rice plants with the aim of producing superior rice varieties in accordance with the problems of farmers in Sumbersalak village. To improve theoretical mastery of the material, the method used is through material presentation activities, discussion sessions and evaluation. To facilitate the transfer of mastery of plant crossing skills in the field to target farmers, the direct practice method is used. The results of the service evaluation show that all target audiences have experienced a change in mastery of knowledge from not knowing and not understanding to knowing and understanding how to cross rice plants